Barriers to accessing and using contraception in highland Guatemala: the development of a family planning self-efficacy scale - Richardson E; Allison KR; Gesink D; Berry A (Dove Medical Press, 2016)
Emma Richardson,1 Kenneth R Allison,1,2 Dionne Gesink,1 Albert Berry3 1Dalla Lana School of Public Health, University of Toronto, 2Public Health Ontario, 3Department of Economics, Munk Centre for International Studies, University of Toronto, Toronto, ON, Canada Abstract: Understanding the persistent inequalities in the prevalence rates of family planning and unmet need for family planning between indigenous and nonindigenous women in Guatemala requires localized explorations of the specific barriers faced by indigenous women. Based on social cognitive theory, elicitation interviews were carried out with a purposive sample of 16 young women, aged 20–24 years, married or in union, from the rural districts of Patzún, Chimaltenango, Guatemala. Content analysis was carried out using the constant-comparison method to identify the major themes. Based on this qualitative study, the following barriers are incorporated into the development of a self-efficacy scale: lack of knowledge about and availability of methods, fear of side effects and infertility, husbands being against family planning (and related fears of marital problems and abandonment), pressure from in-laws and the community, and the belief that using contraception is a sin. This is the first evidence-informed self-efficacy scale developed with young adult, indigenous women that addresses the issue of family planning in Latin America. Keywords: indigenous, marginalized populations, elicitation interviews, social cognitive theory